The Use of Partograph Bugis Midwives Application as a Learning Media for Normal Labor Care by Lecturers and Land Preceptor - Musmir Haeriah; Mardiana Ahmad; Wardihan Sinrang; Syafruddin Syarif (Journal La Edusci, 2020)
This article aims to discuss the design of a web-based Bugis Midwife application as a learning medium for normal childbirth care for lecturers in terms of improving the skills of providing normal delivery care and filling out student partographs and SOAP before going to the field. The type of research used in this research is Research and Development (RnD). The test analysis uses the experimental design model One Group pretest - posttest Design to see whether the application of web-based Bugis Midwives can be better in improving the provision of normal delivery care for students, with a sample of 40 students divided into two groups, a small sample of 10 people and a sample 30 people then analyzed the data using the Wilcoxon Test on SPSS. The results of the posttest after using the application for 3 weeks showed that there were 28 students who scored above 75 with the pass category (93.33%) and there were 2 students who scored below 75 with the category of still needing guidance (6.66%). Furthermore, based on the Wilcoxon test, the results obtained were P value 0.00 <0.05, which means that there is a significant difference between the pretest and posttest scores with the pretest average value of 74 with a sufficiently increased category in the posttest score to 82 in the good category. Based on the analysis of the test results, there is an increase in student learning outcomes on the post-test scores, so the web-based learning media application of the Bugis Midwife is more effective in increasing the knowledge and skills of students.